Measurement of Nitrous Oxide gas pollution in operating rooms of educational hospitals of Ahvaz Jundishapur University in the year 2012 - Masoumeh Albooghobeish; Dr. Abdolkazem nesisi; Mostafa Fattahi; Shahnam Sedigh Marofi (Iranian Journal of Health, Safety and Environment, 2014)
Nitrous Oxide gas can affect the patient and also cause chronic complications in operating room staff in the short term. In the current survey, we measured the Nitrous Oxide gas levels in the operating room of the educational hospitals of the Ahvaz Jundishapur Medical University. 576 samples were taken from 32 operating rooms through 4 months. Sampling was done in 3 different working times (8:30-9:00, 10:30-11, 12:30-13:00) from 6 different sites in the operating room. Portable infrared spectrophotometer was used for measuring the concentration of nitrous oxide. The apparatus was calibrated by Nitrous Oxide gas capsule before each reading. Variance analysis was used to compare the means of Nitrous Oxide levels between places of sampling in the operating rooms. There was a significant difference between these amounts (p≤0.00). Then LSD analysis was used to locate the variation factor. The exhaust of the anesthesia machine was the most noted place (p≤0.0001) and the other places did not show significant differences. There was a significant difference between measurements recorded when the air-conditioning system was on or off and if there was an air-conditioning system or not. These differences were observed at all the measurement times. According to the results from the current study, levels of Nitrous Oxide in operating rooms were higher than that recommended by international organizations (25 ppm) and it appears that exposure to this amount of gas could be potentially harmful for staff. It is recommended to take special safety measures and prevent the gas to be increased in the operating room using air conditioning and proper ventilation of the room.